Comparison between Eustachian tube angle and length in chronic otitis media and contralateral ear - Erlangga, Eggi; Wahyudiono, Ahmad Dian; Yueniwati, Yuyun; Setijowati, Nanik (Oto Rhino Laryngologica Indonesiana, 2023)
Background: Chronic suppurative otitis media (CSOM) is still a significant public health problem, especially in developing countries. Eustachian tube dysfunction is one of the factors that influence the occurrence of CSOM. The pathogenesis of acute and chronic otitis media is initiated by negative pressure in the middle ear. One theory of the event of CSOM is the continuum theory. The eustachian tube as one of the factors that influence the occurrence of CSOM has been proven from various studies comparing CSOM patients and the average population and CSOM with and without cholesteatoma. With the advanced technology, CT scan helps diagnose pathological conditions in the ear as a diagnostic tool and evaluation modality. CT scan imaging with a multiplanar reconstruction technique can provide a clear image of the anatomical shape of the Eustachian tube. Objective: This study aims to determine the relationship between the angle and length of the Eustachian tube in the ear with CSOM and the contralateral ear's angle and length. Method: An analytic study with a cross-sectional design involving 30 samples of CSOM patients with the contralateral ear. The measurement of the angle and length of the Eustachian tube using the multiplanar HRCT temporal reconstruction technique. Result: Statistical analysis with paired t-test showed that the Eustachian tube angle was significantly more horizontal in the CSOM ear than the contralateral ear (p<0.05). Eustachian tube length was shorter in CSOM than contralateral (p<0.05). Conclusion: The angle of the eustachian tube in the CSOM ear is smaller (more horizontal) and shorter than the contralateral ear.